Qualidade química e ciclagem de nutrientes em plantas de cobertura de inverno - Rontani, Fagner Augusto (2020)
Straw production for the system and assessments of nutrient release from plant residues added to the soil by cover crops allow for a better understanding of the supply of nutrients to the soil and also to crops of commercial interest. Thus, article I aimed to evaluate the effect of the proportions in consortium of black oat cover crops with turnip and peas mixed with or without nitrogen supplementation on the mass production potential, residual maintenance of organic carbon (C) and C/N ratio. As a complement to the evaluations, Article II was carried out, where the objective was to evaluate the availability of nitrogen, phosphorus and potassium over the decomposition time of black oat (Avena strigosa), forage turnip (Raphanus sativus L.) and vetch (Vicia sativa L.). The experimental design of articles I and II was the same, being in randomized blocks with four replications, arranged in a two-factorial scheme at the first moment of the installation of the experiment, changing to three-factorial when the plant residues were submitted to decomposition evaluation. Being factor A consortia, factor B proportions and factor C epochs, being six evaluation periods. The main crops were turnip (Raphanus sativus L.), black oats (Avena strigosa Schieb) and vetch (Vicia sativa L.), which were sown in different plant proportions, with 100/0 (black oat monoculture), 75/25, 50/50, 25/75 and 0/100 (turnip or vetch monoculture). Also, in the associations of black oats and turnip, fertilization with 0 and 70 kg ha-1 of N. was tested. The source of N used was urea with 46% of N, with 70 kg ha-1 of N. observed results, it was found that the cover plants had different effects for the evaluations carried out, where the proportions and times of evaluations showed significant difference for at least one tratments in the evaluations of dry mass (DM), carbon (C), nitrogen (N), phosphorus (P) and potassium (K).